Removing bias towards World Englishes: The development of a Rater Attitude Instrument using Indian English as a stimulus. (July 2016) - Hsu, Tammy Huei-Lien
This study explores the attitudes of raters of English speaking tests towards the global spread of English and the challenges in rating speakers of Indian English in descriptive speaking tasks. The claims put forward by language attitude studies indicate a validity issue in English speaking tests: listeners tend to hold negative attitudes towards speakers of non-standard English, and judge them unfavorably. As there are no adequate measures of listener/rater attitude towards emerging varieties of English in language assessment research, a Rater Attitude Instrument comprising a three-phase self-measure was developed. It comprises 11 semantic differential scale items and 31 Likert scale items representing three attitude dimensions of feeling, cognition, and behavior tendency as claimed by psychologists. Confirmatory factor analysis supported a two-factor structure with acceptable model fit indices. This measure represents a new initiative to examine raters' psychological traits as a source of validity evidence in English speaking tests to strengthen arguments about test-takers' English language proficiency in response to the change of sociolinguistic landscape. The implications for norm selection in English oral tests are also discussed.